A study of motivation for achievement and sportsmanship for male and female students of the College of Physical Education and Sports Science at Baghdad University and the relationship between them - Muhsen, Tamadher abdulaziz; Ameen, Ban Adnan Mohammed; Alkreem, khuloud liayth Abd; Muhsen, Muroj (International Journal of Psychosocial Rehabilitation, 2020)
The research sample consisted of 195 male and female students from the College of Physical Education and Sports Science at the University of Baghdad, they were randomly chosen, and the researchers used the Mathematical Spirit scale and the motivation scale for achievement. The research aimed to know the levels of students in these two scales as well as the relationship between them. There were high levels of motivation for achievement and in the mathematical spirit of the research sample with a slight superiority of female students in mathematical circles over students, and no correlation between the two measures appeared.